Role of ion pairs and activity in classification of groundwater for irrigation in Makhmur district - Esmail, Prof. Dr. Akram Othman Esmail; Saheed, MSc. Student Salman Hashm Saheed (Sulaimani Journal for Humanities, 2025)
This investigation was performed during the dry and wet seasons of 2024, which included water chemical analysis for 36 wells in Makhmur District, then classified depending on the mean of chemical analysis for both seasons using some international such as USDA classification (1954), Wilcox (1954) and Ayres and Westcot classification (1994) relying on ions concentrations and their activities. Depending on EC and SAR values the water for (25 ,2.70,61.11and 11.11) % of wells had (C3S1, C3S2, C4S1and C4S2) classes before correcting ion pairs and activities respectively; while depending on activity of ions, the water for (25,2.70, 44.44, 22.22, 2.70 and 2.70) of wells had (C3S1, C3S2, C4S1, C4S2, C4S3 and C4S4) classes. Relying on salinity potential (SP), before correcting ion pairs and activities the water for (9, 3and 24) wells had good, moderate, and poor categories, after correcting ion pair and activities the water for (4) wells changed from bad to moderate class. On the other hand, referring to Ayers and Westcot (1994) and relying on sodium adsorption ratio values the water for (14,17 and 5) wells had no restriction, slight to moderate restriction and severe restriction of use respectively before ion pair and activities correction. While after correcting ion pairs and activities the water for (12,19 and 5) wells had no restriction, slight to moderate restriction and severe restriction of use respectively that caused change two wells to change from class one to class two. Depending on bicarbonate concentration the water for two wells changed from slightly to moderate class to no restriction of use after correcting ion pairs plus activities. Decrease in risk of saline water for irrigation due to converting the water classes towards the better categories. The main results explained the role of ion pairs and activities in conversion the water from class to another then decrease the salinity risk for irrigation use.
Keywords: Groundwater; Water classification; Ion pairs; Activity; Makhmur district